Synthesis and characterization of natural Ca(OH)2/KF superbase catalyst for biodiesel production from palm oil - I. F., Nurcahyo; Wijaya, Karna; Triyono; Budiman, Arief; Yap, Taufiq Yun Hin (Oriental Scientific Publishing Company, 2018)
The natural Ca(OH)2/KF superbase catalyst was synthesized by grinding and calcinations with a rapid thermal annealing method. It was applied to transesterification of palm oil into biodiesel. The effect of molar ratio Ca(OH)2 to KF and calcinations temperature on the catalyst character and the catalytic activity was investigated. The catalysts were characterized by XRD, FTIR, CO2-TPD, surface area, and TGA. The results indicated that natural Ca(OH)2 reacted to KF in forming monoclinic and orthorhombic KCAF3. The monoclinic KCF3 was produced by reaction between Ca(OH)2 and KF, where as the orthorhombic KCaF3 was produced by reaction between CaCO3 impurities and KF. The best catalyst was natural Ca(OH)2/KF with molar ratio of Ca(OH)2 to KF 0.8:1 and calcinations at 500oC. The catalyst was able to convert 97.6 % oil into biodiesel within 1 minute at 5 % catalyst, molar ratio oil/methanol of 1/12, reaction temperature of 65oC.